Nomad Century: How to Survive the Climate Upheaval - Gaia Vince (UK Penguin Random House, 2023)
An urgent investigation of the most underreported, seismic consequence of climate change - how it will force us to change where - and how - we liveWe are facing a species emergency. With every degree of temperature rise, a billion people will be displaced from the zone in which humans have lived for thousands of years. While we must do everything we can to mitigate the impact of climate change, the brutal truth is that huge swathes of the world are becoming uninhabitable. From Bangladesh to Sudan to the western United States, and in cities from Cardiff to New Orleans to Shanghai, the quadruple threat of drought, heat, wildfires and flooding will utterly reshape Earth's human geography in the coming decades. In this rousing call to arms, Royal Society Science Prize-winning author Gaia Vince demonstrates how we can plan for and manage this unavoidable climate migration.
Including Index
Keywords: Storm -- Climate